Features of nervous system in children with irritable bowel syndrome - O. K. Botvin’yev; A. V. Yeremeyeva; Ali Mohamed Gamal Eldin Mansur; V. B. Lyalikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To reveal features of nervous system in children with various variants of irritable bowel syndrome (IBS).Material and methods. Overall 125 patients with IBS in the age of 3 to 17 years were included in original study. Features of pre- and postnatal past history were investigated, trigger factors promoting onset or relapse of this disease were analyzed. Assessment of initial state of autonomous nervous system by electroencephalography and heart rate variability measurement (HRV) was carried out.Results. Investigation of the state of autonomous nervous system in children with IBS, was carried out by HRV, objectively demonstrated disorder of autonomous body supply in motor and evacuatory dysfunction of gastro-intestinal tract (constipation, diarrhea).Conclusions. Disorder of autonomous function of the body is objectively detected at various clinical variants of IBS at children.